Same-sex male couples and single men having children using assisted reproductive technology: a quantitative analysis. Issue 5 (May 2021) - Hemalal, Shilini; Yee, Samantha; Ross, Lori; Loutfy, Mona; Librach, Clifford
Abstract: Research question: How do same-sex male couples (SSMC) and single men perceive their experience of using assisted reproductive technology (ART) in Canada; what factors contribute to their experience and the decisions made throughout the ART process? Design: This cross-sectional study used an anonymous online survey to gather exploratory data (between August 2018 and August 2019) about participant experience and decision-making considerations, for SSMC and single men internationally who had undergone ART in Canada. The survey was accessed by 145 individuals; 98 participants were included in the final analysis. Statistical Package for the Social Sciences (SPSS) was used for quantitative analysis. Results: Four out of five participants had a positive overall experience of using ART in Canada. Having the social support of knowing others who had previously pursued ART, and needing to work with multiple egg donors, were found to affect overall experience significantly. Agencies were the most common way for intended parents to connect with third parties. Major factors men considered when choosing an egg donor included medical history, physical attributes, personality and temperament, ethnicity, and education; they tended to select gestational surrogates who had similar lifestyle values to themselves. Most coupled survey respondents created embryos using each partner's spermatozoa (73.6%). Conclusions: This exploratory study expands on limited knowledge of the current topic, identifying key areas for future research. Most SSMC and single men, domestic and internationally, had a positive experience pursuing ART in Canada to have children. Research on the experiences of SSMC and single men and decision-making considerations should continue.